2009
DOI: 10.1103/physrevb.79.075106
|View full text |Cite
|
Sign up to set email alerts
|

Band offsets of a ruthenium gate on ultrathin high-κoxide films on silicon

Abstract: grown on silicon͒ and their shifts upon sequential metallization with ruthenium have been measured using synchrotronradiation-excited x-ray, ultraviolet, and inverse photoemissions. From these techniques, the offsets between the valence-band and conduction-band edges of the oxides, and the ruthenium metal gate Fermi edge have been directly measured. In addition the core levels of the oxides and the ruthenium have been characterized. Upon deposition, Ru remains metallic and no chemical alteration of the underly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…For a number of oxides, S and the position of the CNL have been calculated theoretically (3,5). Using these calculated parameters along with experimental measurements of φ M , χ O and the oxide gap, we have shown in a recent work that for the case of Ru metallization of high-κ oxide films, that the CBO predicted by the MIGS model is in excellent agreement with those obtained experimentally (12).…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…For a number of oxides, S and the position of the CNL have been calculated theoretically (3,5). Using these calculated parameters along with experimental measurements of φ M , χ O and the oxide gap, we have shown in a recent work that for the case of Ru metallization of high-κ oxide films, that the CBO predicted by the MIGS model is in excellent agreement with those obtained experimentally (12).…”
Section: Introductionsupporting
confidence: 52%
“…Although the mechanism of Al oxidation is still unclear, this behavior as been observed during Al deposition on a HfO 2 /Ge stacks with the concomitant reduction of an interfacial GeO x (17). Not central to our discussion, but worthy of note is that Si 2p core levels shifts are observed at the oxide/semiconductor interface,, indicating that the energy alignment of the entire stack reorganizes upon metal deposition (12,18). For a better description of these processes, higher photon energy XPS could enable tracking chemical and energy alignment modifications of buried layers across the entire stacks.…”
Section: Mos Stacks Chemistry and Metallizationmentioning
confidence: 59%
“…As such, the CNL used will be rescaled accordingly using the theoretical CNL (i.e., CNL th ) via the relation, CNL ¼ CNL th (E g,meas /E g,th ). 20 This is valid because the position of the CNL is directly affected by the relative position in energy of the occupied and unoccupied states, as dictated by the band gap.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…Moreover, studies on atomic layer deposition of Ru from advanced precursors such as (methylcyclopentadienyl)(pyrrolyl)ruthenium on SrTiO 3 [15] have revealed that the growth of Ru on such materials is poorly controlled unless plasma-assisted cleaning of underlying oxide film is applied despite the possible structural damage of the oxide surface. Nevertheless, noble metal electrodes (Ru, RuO 2 ) are of significant importance [16,17] despite the related increase in processing costs. Notable amount of studies on Ru so far have been devoted to the issues related to the nucleation of ruthenium thin films as well as to the parametrization of growth processdependence of the growth rate and roughness on growth temperature, pressure and time [2,[18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%